An examination of assessment models for the eastern North Pacific gray whale based on inertial dynamics - Punt, Andre E.; Allison , Cherry; Fay, Gavin (J. Cetacean Res. Manage., 2023)
Bayesian assessments of the eastern North Pacific stock of gray whales are conducted using the standard BALEEN II model and the inertia model developed by Witting (2000; 2001; 2003). The analyses confirm the increase in gray whale population size since 1968, but indicate that catches up to 256 animals per annum will lead to population decline if the inertia model is correct. However, analyses based on the standard BALEEN II model with a starting year of 1930 or 1968 fit the calf count data better than the inertia model, and indicate a population at its (current) equilibrium level and that the current catches are sustainable. The results of both the BALEEN II model and the inertia model are sensitive to the choice of the functional form used to represent density-dependence and those of the inertia model to the starting year for the analyses.